PHYTOCHEMICALS OF Tinospora crispa WITH ANTICANCER AND ANTIVIRAL ACTIVITIES: A REVIEW - BIN ABDULL RASAD, MOHAMMAD SYAIFUL BAHARI; BINTI PARJAN, MIZAN KAMALINA (International Journal of Allied Health Sciences, 2023)
Introduction: The discovery of new anticancer and antiviral agents from plants have drawn a lot of attention due to their vast spectrum of biological and therapeutic properties in which many evidences proved that the plants and plant-derived products are effective and safe for treating and managing various types of diseases and illnesses. Phytochemicals in plants are promising anticancer and antiviral agents which may improve the treatment efficiency and decrease the adverse reactions. Tinospora crispa plant is traditionally used to treat various types of illnesses and diseases. Many studies reported that T. crispa has anti-proliferative and anti-angiogenesis activities as well as antiviral activities. Objective: The purpose of the study was to compile and identify the phytochemicals of T. crispa with anticancer and antiviral properties. Method: The online databases that have been utilized in this study were Google Scholar, Science Direct and PubMed. The selection of articles was managed based on PRISMA 2009 and was assessed based on inclusion and exclusion criteria as specified. From total of 705 articles screened, 11 relevant articles were chosen. Result: T. crispa compounds with potential anticancer activity were tetrandrine and alkaloid, while T. crispa compounds with potential antiviral activities were berberine, ndrostanene-4-ne, 2-imino-1-(4-methoxy-6-dimethylamino- 1,3,5-triazin-2-yl), spiro[4,5] dec-6-en-1-ol, 2,6,10,10-tetramethyl, 3?-hydroxy-5- cholen-24-oic acid, ndrostane-17-one, 3-ethyl-3-hydroxy-(5?), camphenol, (?)- globulol, yangambin, nordazepam, trimethylsilyl derivative and benzeneethanamine. Meanwhile, the compounds that may have potential for both anticancer and antiviral activities were magnoflorine, ?-amyrin, ?-sitosterol and lupeol. Conclusion: This study found 52 compounds from T. crispa, including alkaloid, terpenes, phenolic compounds, glycosides and alcohol that exhibited anticancer and antiviral activities.